Pneumococcal serotypes in sputum isolates during acute respiratory illness in Edinburgh. Issue 8 (August 1987) - Gould, G A; Rhind, G B; Morgan, A D; Williamson, G; Calder, M A
Abstract : During the years 1978-83 serotyping was carried out on all sputum isolates of pneumococci obtained from patients in the chest wards of the City Hospital, Edinburgh. In 402 patients with acute respiratory illness the peak isolation rates occurred from January to April, and the serotype distribution was similar to that seen in previous UK studies, the commonest types being 3, 6, 9, 19, 23, and 8. The overall mortality rate was 8.7%, the serotype distribution in fatal cases reflecting the distribution of the whole group. The presence of mixed infection, predominantly with Haemophilus influenzae, was associated with a lower mortality rate of 3.5%. Nearly all patients (92%) were either elderly or had a chronic underlying disease and only one death occurred in a patient under 70 years who had no pre-existing disease. Of the pneumococcal serotypes isolated from the 292 patients with chronic chest disease, 82% are included in the new 23 valent pneumococcal vaccine and the efficacy of this needs to be assessed further in high risk patients.